Effects of Graded Whey Supplementation During Extreme-Volume Resistance Training - Haun, Cody T.; Vann, Christopher G.; Mobley, Christopher B.; Roberson, Paul A.; Osburn, Shelby C.; Holmes, Hudson M.; Mumford, Petey M.; Romero, Matthew A.; Young, Kaelin C.; Moon, Jordan R.; Gladden, L. Bruce; Arnold, Robert D.; et al. (Frontiers in Nutrition, 2018)
We examined hypertrophic outcomes of weekly graded whey protein dosing (GWP) versus whey protein (WP) or maltodextrin (MALTO) dosed once daily during 6 weeks of high-volume resistance training (RT). College-aged resistance-trained males (training age=5±3 yrs; mean±SD) performed 6 weeks of RT wherein frequency was 3 d/wk and each session involved 2 upper- and 2 lower-body exercises (10 repetitions/set). Volume increased from 10 sets/exercise (week 1) to 32 sets/exercise (week 6), which is the highest volume investigated in this timeframe. Participants were assigned to WP (25g/d; n=10), MALTO (30g/d; n=10), or GWP (25-150 g/d from weeks 1-6; n=11), and supplementation occurred throughout training. Dual-energy x-ray absorptiometry (DXA), vastus lateralis (VL) and biceps brachii ultrasounds for muscle thicknesses, and bioelectrical impedance spectroscopy (BIS) were performed prior to training (PRE) and after weeks 3 (MID) and 6 (POST). VL biopsies were also collected for immunohistochemical staining. The GWP group experienced the greatest PRE to POST reduction in DXA fat mass (FM) (-1.00 kg, p<0.05), and a robust increase in DXA fat- and bone-free mass [termed lean body mass (LBM) throughout] (+2.93 kg, p<0.05). However, the MALTO group also experienced a PRE to POST increase in DXA LBM (+2.35 kg, p<0.05), and the GWP and MALTO groups experienced similar PRE to POST increases in type II muscle fiber cross-sectional area ( +300 μm2). When examining the effects of training on LBM increases (ΔLBM) in all participants combined, PRE to MID (+1.34 kg, p<0.001) and MID to POST (+0.85 kg, p<0.001) increases were observed. However, when adjusting ΔLBM for extracellular water (ECW) changes, intending to remove the confounder of edema, a significant increase was observed at PRE to MID (+1.18 kg, p<0.001) but not MID to POST (+0.25 kg; p=0.131). Based upon DXA data, GWP supplementation may be a viable strategy to optimize body composition during high-volume RT. However, large LBM increases observed in the MALTO group preclude us from suggesting that GWP supplementation is clearly superior in facilitating skeletal muscle hypertrophy. With regard to the implemented RT program, ECW-corrected ΔLBM gains were largely dampened, but still positive, in resistance-trained participants when RT exceeded 20 sets/exercise/wk.